Algorithm for Optimal Supplement of Train Traffic Schedule - Mišauskaitė, I. (Elektronika ir Elektrotechnika, 2006)
Article analyses a problem of train traffic schedule optimal addition according to minimum overall expenditure criteria. Task is to analyze optimal insertion of an additional train track into already made schedule. The methodology is all-right applicable for ad hoc requests submission. Handling importance of ad hoc requests is emphasized in EU directive 2001/14/EU. Task can be solved applying Monte-Carlo, genetic algorithms, variants reselection methods or methods of the shortest (according to waste) way in graphs. All these methods are equally exact and can be implemented with modern computers with short enough time consumption. Ill. 2, bibl.8 (in English; summaries in English, Russian and Lithuanian).